Religion, cognitive style, and rational thinking. (August 2020) - Baron, Jonathan
Highlights: Social liberalism, reflective thinking, and utilitarian judgments all correlate positively but negatively with religion. It is unlikely that these correlations result from the way subjects do the experimental tasks. One possibility is that reflective cognitive style leads, over time, to social liberalism and reduced religious belief. Or, studies sample different cultures, some influenced by the Enlightment and others based on pre-Enlightment doctrines. Abstract : Recent research has reported strong correlations among trait measures of religious belief, social conservatism (as a political ideology), deontological reasoning about morality, and (negatively) measures of rational cognitive style. I suggest many modern societies are divided between two cultural groups who think differently and have different beliefs, with one group being influenced by the Enlightenment and the other still accepting older beliefs and ways of thinking, often based on religious traditions. A plausible alternative account of many results is that individual differences in cognitive style affect the course of individual development, and actively open-minded thinking may lead to abandonment of religion. Here, I review some of the recent research on these correlations.